Miro1 R272Q disrupts mitochondrial calcium handling and neurotransmitter uptake in dopaminergic neurons - Schwarz, Lisa; Sharma, Karan; Dodi, Lorenzo D.; Rieder, Lara-Sophie; Fallier-Becker, Petra; Casadei, Nicolas; Fitzgerald, Julia C. (Frontiers in Molecular Neuroscience, 2022)
The Rho GTPase Miro1, located at the mitochondrial outer membrane is known to properly distribute mitochondria to synapses, aid calcium buffering and initiate PINK1-Parkin mediated mitophagy. Several heterozygous RHOT1/Miro1 variants were identified in sporadic Parkinson’s disease patients. Miro1 R272Q is located within a calcium binding domain, but the functional outcome of this point mutation and its contribution to the development of disease are unclear. To address this, we introduced a heterozygous RHOT1/Miro1 R272Q point mutation in healthy induced pluripotent stem cells. In dopaminergic neurons, Miro1 R272Q does not affect Miro1 protein levels, CCCP-induced mitophagy, nor mitochondrial movement yet causes the fragmentation of mitochondria with reduction of cristae and ATP5A. Inhibition of the mitochondrial calcium uniporter phenocopied Miro1 R272Q cytosolic calcium response to Thapsigargin in active neurons, a similar effect was observed during the calcium buffering phase in Miro1 knockdown neuroblastoma cells. Altered mitochondrial calcium regulation is associated with reduced mitochondrial respiration and reduced catecholamine neurotransmitter uptake. Synaptic changes are not coupled to dopamine distribution or dopamine transporters but are linked to Miro1 R272Q-related calcium handling via the mitochondria concomitant with defective dopamine regulation at the mitochondrial surface by monoamine oxidase. We conclude that the Miro1 R272Q heterozygous point mutation dampens mitochondrial-calcium regulation and mitochondrial capacity via events at the outer membrane that are sufficient to disrupt dopaminergic function.